(untitled) (Research, Society and Development, 2022)
It is believed that the association of nitrogen fixing bacteria minimizes the adverse effects caused by environmental stresses in cowpea cultivated in the semiarid region, thus, the objective was to evaluate the responses of different cowpea genotypes inoculated with recommended strains, irrigated with different depths of saline water. The experiment was carried out at the Serra Talhada Academic Unit (UFRPE/UAST). A randomized block design was used, in subdivided plots (4 x 2 x 3), whose treatments were different irrigation depths (25, 50, 75 and 100 % of crop evapotranspiration - ETc), associated with two bean genotypes. cowpea (IPA 206 (G1) and BRSTumucumaque (G2), in addition to two inoculants (BR 3262 (I1) and BR 3267 (I2) and treatment without inoculation. Irrigation depths with their maximum application (100%) provided greater accumulation of phytomass. In relation to nodulation, the water depth of 25% was the most indicated. The G1 genotype provided productivity of 1.95 t ha-1 and the G2 2.12 t ha-1 averages much higher than Nacional, which is around 400 kg ha–1. The activity of the enzyme Polyphenoloxidase (PPO) was increased with the 100% depth in G2, regardless of the inoculant and the depth used. The activity of e Peroxidase (POD) was higher with 100% of irrigation water in relation to the conditions of 25%, for the two genotypes. The G2 genotype presented more phenolic compounds in relation to o to G1, in the conditions of maximum water depth (100%), when comparing the content of phenolic compounds, which may be a response to water and saline stress.